The Role of the Palu City Government in Empowering UMKM in Palu City (Jurnal Studi Inovasi Pemerintahan, 2024)
This research aims to describe how to evaluate the success of the Palu City Government's role in empowering UMKM in Palu City. This research uses the theory of Ryaas Rasyid (2010) in Muhadam Labollo on the Role of Government. This research uses a qualitative research approach with descriptive research type. Data collection techniques use observation, interview and documentation techniques. The research results show the success of the government's role through the government's role as a regulator, the government's role as a dynamist, and the government's role as a facilitator. Although there is one role of government that has not been successful, namely the role of government as a catalyst because there are obstacles regarding the understanding of UMKM actors in utilizing technology and marketing the products they have. However, the government's strategic role in providing training and also assistance in the form of business capital has provided opportunities for business actors who want to develop their businesses. The positive impact can be seen in the empowerment of UMKM actors who have been given training and outreach regarding UMKM development. Suggestions include how the Palu City government can disseminate more information regarding how to utilize technology in marketing access to products owned by UMKM players. So, in realizing the government's role, it is hoped that it can provide benefits for UMKM in developing their businesses.